Proteomic profiling of the phosphoproteins in the rat thalamus, hippocampus and frontal lobe after propofol anesthesia - Tang, Jing (BioMed Central, 2014)
BACKGROUND: Propofol is a safe and effective intravenous anesthetic that is widely used for the induction and maintenance of anesthesia during surgery. However, the mechanism by which propofol exerts its anesthetic effect remains unknown. The rapid onset of phosphorylation modifications coincides with that of propofol anesthesia. METHODS: Propofol-anesthetized rat models were built and phosphorylated proteins in the thalamus, hippocampus and frontal lobe were enriched the to analyze the changes in these phosphoproteins after propofol anesthesia. RESULTS: Sixteen of these phosphoprotein spots were successfully identified using MALDI-TOF MS and a subsequent comparative sequence search in the Mascot database. Of these proteins, keratin 18 and the tubulin 2c chain are cytoskeletal proteins; keratin 18 and gelsolin are relevant to alcohol drowsiness. Based on Western blot analysis, we also confirmed that the phosphorylation of these proteins is directly induced by propofol, indicating that propofol anesthesia may be relevant to cytoskeletal proteins and alcohol drowsiness. CONCLUSIONS: These identified propofol-induced phosphorylations of proteins provide meaningful contributions for further studying the anesthetic mechanism of propofol.